Impact of knowledge, attitude and anxiety levels about COVID-19 on the quality of life in pregnant women - Gökçe, Şefik; Herkiloğlu, Dilşad (Journal of Surgery and Medicine, 2021)
Background/Aim: Depression and anxiety during pregnancy can lead to pregnancy-related maternal or fetal complications if they are severe or persistent. Therefore, it is important to identify pregnant women who are significantly affected by the COVID-19 pandemic, take the necessary measures or implement rehabilitation programs. This study aimed to determine the feelings, thoughts, attitudes, beliefs, concerns and levels of general depression and anxiety in pregnant women caused by the COVID-19 pandemic and examine the factors that cause mental health disorders. Methods: A total of 85 pregnant women who were followed up in the Gynecology and Obstetrics clinics of our hospital and who were never infected with COVID-19 were included in this cross-sectional study. Pregnant women were asked to fill out a questionnaire about the COVID-19 pandemic, and the Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI) and the Short Form 12-Item Health Survey (SF-12) questionnaires. Results: According to the BDI, 9.4% of the pregnant women had moderate depression, while none had severe depression. According to BAI, 12.9% had moderate anxiety, and 4.7% had severe anxiety. BDI (P=0.001) and BAI (P=0.022) scores were significantly higher, and SF-12 physical role (P=0.004) and SF-12 social functioning (P=0.02) scores were significantly lower in those with a high level of anxiety for their unborn baby. Conclusion: Our findings show that depression and anxiety levels in pregnant women have been high during the COVID-19 pandemic, and that pregnant women are concerned about their own and their babies’ health. Anxiety and depression levels affect the attitude and belief of pregnant women, and all these mental health deteriorations decrease their quality of life.